Nutritional Status and Infant Feeding Practices Adopted by Working Women in Jodhpur City - Fotedar, Ranjana; Lakshminarayana, J; Ramanath, T; Singh, Madhu B (Annals of Arid Zone, 2016)
A survey was conducted on 200 working women from urban area in Jodhpur, mainly to assess their health and nutritional status. Majority of the women reported that working outside home was mainly to improve their living standard. Thirty seven women were from well-to-do families, 52 from Middle Income Group (MIG) and I I I were from Low Income Group (LIG). A large family size and low literacy were found associated with LIG when chi-square test was applied. A significantly low percentage (P) of women were found discarding colostrums in well-to-do group (16.1 %) as compared to MIG (56.1 %) and LIG (59.3%). Delayed supplementation beyond I year was observed for LIG (39.8%), as compared to MIG (12.1 %) and well-to-do (6.5%) families. Similarly, longer duration of breast feeding was seen in women of LIG. Well-to-do women opted for commercial food (55.0%) and had better awareness of supplemental food for infants. while the rest’ opted for traditional food foLsupplementation. A significantly higher percentage (30.5%) of malnutrition (BMI<I8.5) was seen in LIG (P<0.05) as compared to women of other two categories. A lower percentage (20.0%) of obesity was seen in women of LIG. Hypertension was quite low in all the groups. The working women contributed to the family income for improving the living standard, but the nutritional status. infant feeding practices and supplementary feeding differed significantly between the three categories.